ASSOCIATION OF NUTRITIONAL STATUS WITH MENARCHE : A SYSTEMATIC REVIEW - Juliana, Mutia; Tegar Perbawa, Prayudha (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Menarche is the process that takes place when the hypothalamic-pituitary-ovarian (HPO) axis matures. This maturation is dependent on adequate hypothalamic and pituitary function, normal female reproductive anatomy, normal nutrition, and the absence of other long-term disorders. When a woman's reproductive health and overall wellbeing are normal, it is a sign that they are not abnormal. However, the substantial decline in the age at menarche that occurred between the early 19th century and the middle of the 20th century was associated with a significant improvement in nutrition and living conditions brought about by the process of modern civilization. Although genetic factors are responsible for approximately 50–80% of the variation in puberty onset age and milestones, environmental factors also play a role. This article demonstrates that individuals with a poor dietary level reach menarche at a later age. Girls have a greater chance of gaining weight if the foods they consume are high in fat and the nutrients that originate from animal products. It is possible for it to enhance levels of the hormone estrogen, which then supports elevated levels of cholesterol. This cycle continues until the desired effect is achieved.